2014
DOI: 10.1016/j.jacc.2014.07.988
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Interpapillary Muscle Dynamics as an Active Indicator of Mitral Valve and Left Ventricular Interaction in Ischemic Mitral Regurgitation

Abstract: By using cardiac magnetic resonance imaging in humans, we demonstrated that it is the impairment of lateral shortening between the papillary muscles, and not passive ventricular size, that governs the severity of mitral regurgitation. Loss of lateral shortening of IPMD tethers the leaflet edges and impairs their systolic closure, resulting in mitral regurgitation, even in small ventricles. Understanding the lateral dynamics of ventricular-valve interactions could aid the development of new repair techniques fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 20 publications
4
47
0
Order By: Relevance
“…10,17,221,222 The use of 3D echocardiography in experimental studies has proved that global left ventricular dysfunction alone is insufficient to cause IMR. 223225 Displacement and abnormal contraction of the left ventricular wall underlying the papillary muscles, along with decreased shortening of the distance between the papillary muscles, causes mitral leaflet tethering and restricted closure that leads to IMR (Figures 12a,b), 223226 which is referred to as a Carpentier type IIIb lesion. Isolated annular dilation, such as occurs in patients with lone atrial fibrillation, also impairs coaptation (Carpentier type I), but relatively mildly unless the leaflets are tethered at both annular and ventricular ends.…”
Section: Ischaemic Mitral Regurgitationmentioning
confidence: 99%
“…10,17,221,222 The use of 3D echocardiography in experimental studies has proved that global left ventricular dysfunction alone is insufficient to cause IMR. 223225 Displacement and abnormal contraction of the left ventricular wall underlying the papillary muscles, along with decreased shortening of the distance between the papillary muscles, causes mitral leaflet tethering and restricted closure that leads to IMR (Figures 12a,b), 223226 which is referred to as a Carpentier type IIIb lesion. Isolated annular dilation, such as occurs in patients with lone atrial fibrillation, also impairs coaptation (Carpentier type I), but relatively mildly unless the leaflets are tethered at both annular and ventricular ends.…”
Section: Ischaemic Mitral Regurgitationmentioning
confidence: 99%
“…Acute mitral regurgitation necessitating immediate surgery due to complete or sequential papillary muscle (PM) rupture is a rare major adverse cardiac event [2,3]. In the majority of patients, ischemic mitral regurgitation develops gradually due to remodeling of the ischemic myocardium and altered hemodynamic conditions in the left ventricle [4]. Additionally, PM infarction may contribute to the development of ischemic mitral regurgitation by tethering of the chordae and subsequent dysfunction of the PM-chorda-mitral valve complex [5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent comprehensive study involving MRI evaluation of patients with IMR supplemented with an experimental IMR animal model and computational analysis revealed that loss of lateral shortening of inter-papillary distance may be central to the pathogenesis of IMR. 24 Experimental surgical interventions that relocate the posterior papillary muscle toward the septum such as a cinching stitch 25 or inflating balloon 26 have shown promise in controlling IMR. Repositioning of the posterior papillary muscle with an externally adjusted chord anchored at the fibrous trigone as an adjunct to ring annuloplasty has now also found clinical application.…”
Section: Discussionmentioning
confidence: 99%